Pengembangan kampung ekowisata Ayapokiar Tambrauw melalui Tridharma Universitas Papua: Development of Ayapokiar Tambrauw Ecotourism Village Through Tridharma University of Papua - Fatem, Sepus M.; Wambrauw, Yustina L. D.; Arung Padang, Dina; Ayomi, Adomina; Sebayang, Sri R.; Fatem, Desmina F.; Ahoren, Calista; Krey, Sarah D. D. (Fakultas Peternakan Universitas Papua, 2024)
ABSTRACT Community Service “Program Pengembangan Kampung Ekowisata” is a manifestation of the Papua University Higher Education, namely community service. Community service is a form of knowledge that is expressed theoretically in college to be applied in real life in the Ayapokiar village community, so that the knowledge gained can be applied and developed in the life of the wider community. In general, this program is hoped that can contribute to the development of the Cenderawasih bird watching tourist village, especially for improving the welfare of indigenous communities as guardians and owners of forests and the Cenderawasih bird habitat. The activities that was done were: 1) providing food for villagers, 2). health check activities for the community, 3) students carry out teaching activities in elementary school, 4). providing stationery gifts for elementary school children, and 5). ecotourism guide counseling of Paradisea minor. Keywords: Ayapokiar Village; Bird Watching; Community Service; Community Welfare; Ecotourism ABSTRAK Program Pengembangan Kampung Ekowisata di Kampung Ayapokiar Kabupaten Tambrauw merupakan salah satu wujud Tridharma Perguruan Tinggi Universitas Papua. Program ini sebagai bentuk implementasi ilmu teoritis di perguruan tinggi untuk diterapkan dalam kehidupan nyata masyarakat Kampung Ayapokiar sehingga ilmu yang diperoleh dapat dikembangkan dalam kehidupan masyarakat luas. Program yang dilakukan adalah: 1) pemberian bahan makanan kepada masyarakat, 2) pemeriksaan kesehatan gratis, 3) mahasiswa mengajar di SD YPPK Ayapokiar, dan 4) Pembagian alat tulis untuk anak SD YPPK Ayapokiar, dan 5) penyuluhan pemandu ekowisata burung Cenderawasih kecil. Secara umum, program ini diharapkan dapat berkontribusi terhadap pengembangan kampung ekowisata pengamatan burung Cenderawasih kecil sekaligus bagi peningkatan kesejahteraan masyarakat adat sebagai pemilik hutan habitat burung Cenderawasih kecil di Kampung Ayapokiar, Distrik Miyah, Kabupaten Tambrauw. Kata kunci: Ekowisata; Kampung Ayapokiar; Kesejahteraan Masyarakat; Pengamatan Burung; Pengabdian Masyarakat